Noha Beauty Cosmetic E-Commerce System (NBCeS) based on online shopping behaviour / Nursyahidatul Akmal Hassim - Hassim, Nursyahidatu (2019)
Noha Beauty Cosmetic E-Commerce System (NBCeS) based on online shopping behaviors theory is a prototype ordering system website where target user can use the system for order the cosmetic product via online. NBCeS is develop for increase the efficiency the current business process. Beside increase the efficiency, by implementing this system would give may benefits to the target user of the system, which is customer, staff and admin. This system derived from the current business process problem faced by Noha Beauty Cosmetic. The development process for this system based on online shopping behavior theory. The development process involved in this project is by adapting the Waterfall Model of SDLC. The methodology has sic sequential step that need to be follow to meet the requirement. The system has been evaluating by using the unit testing planning for the target user of the system. Hence, the functionality and usability of the system was tested in order to complete the process development.